Dynamic model of a vehicle moving in the urban area - Makaras, Rolandas; Sapragonas, Jonas; Keršys, Artūras; Pukalskas, Saugirdas (Transport, 2011)
The peculiarities of constructing a model of an individual vehicle moving along the urban street are investigated. The aim of the study is to construct a dynamic vehicle-environment-driver model, which enables to implement the situation ‘an individual vehicle moving along urban streets’, taking into consideration a concrete type of a vehicle, its loading, driver's behavior, peculiarities of external characteristics of internal combustion engines run on traditional or alternative fuel as well as the use of hybrid power plants.First Published Online: 12 Apr 2011